2009
DOI: 10.1016/j.molcel.2009.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosomes Have Six Mitochondrial DNA Helicases with One Controlling Kinetoplast Maxicircle Replication

Abstract: Summary Kinetoplast DNA (kDNA), the trypanosome mitochondrial DNA, contains thousands of minicircles and dozens of maxicircles interlocked in a giant network. Remarkably, Trypanosoma brucei's genome encodes eight PIF1-like helicases, six of which are mitochondrial. We now show that TbPIF2 is essential for maxicircle replication. Maxicircle abundance is controlled by TbPIF2 level, as RNAi of this helicase caused maxicircle loss and its overexpression caused a 3- to 6-fold increase in maxicircle abundance. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
106
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(114 citation statements)
references
References 44 publications
(68 reference statements)
6
106
0
2
Order By: Relevance
“…The only mitochondrial protease that has been shown to regulate kDNA replication is TbHslVU (25). This bacterial-like protease regulates maxicircle replication through the degradation of the helicase TbPIF2 (27). To determine if proteolytic degradation plays a role in the regulation of POLID-PTP localization patterns, we inhibited protein synthesis using 100 g/ml of CHX during a time course of 6 h. For this experiment we generated a cell line coexpressing POLID-PTP and PIF2-Myc, and we monitored protein levels by immunoblotting.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The only mitochondrial protease that has been shown to regulate kDNA replication is TbHslVU (25). This bacterial-like protease regulates maxicircle replication through the degradation of the helicase TbPIF2 (27). To determine if proteolytic degradation plays a role in the regulation of POLID-PTP localization patterns, we inhibited protein synthesis using 100 g/ml of CHX during a time course of 6 h. For this experiment we generated a cell line coexpressing POLID-PTP and PIF2-Myc, and we monitored protein levels by immunoblotting.…”
Section: Resultsmentioning
confidence: 99%
“…These data suggested that POLID also has an important role in maxicircle replication (6). So far, only two proteins have definitive roles in maxicircle replication, the primase PRI1 and the helicase PIF2 (17,27). Significant questions about maxicircle replication remain unanswered, including what is the maxicircle replicase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A plethora of proteins involved in kDNA replication have been studied in T. brucei, including six helicases (25)(26)(27)40), two DNA ligases (10), two primases (19,20), a topoisomerase IA (40), a topoisomerase II (50), and five DNA polymerases (Pols) (4,7,21,35). The involvement of multiple DNA polymerases in kDNA replication distinguishes this process from replication of other mitochondrial genomes, which depend solely upon DNA polymerase ␥, a family A DNA polymerase.…”
mentioning
confidence: 99%